2021
DOI: 10.3390/agronomy11040775
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Salicylic Acid on the Performances of Salt Stressed Strawberry Plants, Enzymes Activity, and Salt Tolerance Index

Abstract: The influence of salicylic acid (SA) on growth, yield, fruits’ quality and enzymes’ activities was monitored in strawberry plants cv. Camarosa grown under salinity stress via two pot experiments in two successive years of 2018 and 2019. The examined concentrations of SA were 30, 60, and 90 ppm, which foliary applied in addition to control (sprayed with water), while the used levels of salinity were 20, and 40 mM as NaCl as irrigation application in addition to control (without salinity). The results showed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…SA influences numerous important physiological functions in plants, such as increasing the uptake of nutrients and decreasing Na + concentrations under salt stress [ 22 , 23 ]. Similarly, [ 26 ] researchers have reported that increasing the concentration of SA up to 90 ppm mitigates the negative effect of salinity on N, P, and K concentrations and decreases the Na + content of strawberry leaves under high levels of NaCl (40 mM). It was reported that the foliar supplementation of SA at 0, 1.0, 1.5, and 2.0 mM reduced the Na uptake of plants and was efficient in enhancing nutrient uptake by cotton seedlings grown under 150 mM NaCl [ 28 ].…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…SA influences numerous important physiological functions in plants, such as increasing the uptake of nutrients and decreasing Na + concentrations under salt stress [ 22 , 23 ]. Similarly, [ 26 ] researchers have reported that increasing the concentration of SA up to 90 ppm mitigates the negative effect of salinity on N, P, and K concentrations and decreases the Na + content of strawberry leaves under high levels of NaCl (40 mM). It was reported that the foliar supplementation of SA at 0, 1.0, 1.5, and 2.0 mM reduced the Na uptake of plants and was efficient in enhancing nutrient uptake by cotton seedlings grown under 150 mM NaCl [ 28 ].…”
Section: Discussionmentioning
confidence: 93%
“…The decrease of plant growth under salt stress may be due to the reduction in cell division and elongation [ 38 ]; there is also a destructive impact of NaCl on different physiological pathways and molecular changes through impaired photosynthesis, nutrient imbalances, stomatal impedance to water flow, alterations in the ultrastructure of chloroplasts and mitochondria (which affect the natural metabolism), and hormonal imbalances [ 39 , 40 ]. Earlier studies [ 25 , 26 , 28 , 41 ] showed that SA could reduce salt damage in various plants. The exogenous application of SA is expected to control stomatal opening under stress, and this decreases transpiration and water loss, sustains turgor, and controls plant growth and productivity under stress conditions [ 33 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, environmental stimuli such as light, temperature, water, and other factors are in charge of stimulating these mechanisms [8]. Roshdy and colleagues reported high value of CAT and POX activities of strawberry leaves by increasing salinity levels and SA concentration [59]. There are some reports about the effects of SA on transit accumulation of ABA and control of antioxidant enzymes activity on the response of the plants to drought stress [60].…”
Section: Resultsmentioning
confidence: 99%